Gender Equity in Labor Market Opportunities and Aggregate Technical Efficiency: A Case of Equity Promoting Efficiency - Gautam Hazarika; Maroula Khraiche; Levent Kutlu (Institute of Labor Economics (IZA), 2023)
This study applies a panel data stochastic frontier analysis to country data towards examining the effect of gender equity in labor market opportunities upon efficiency in the production of GDP. It finds that aggregate technical efficiency is improved by a widening of women's labor market opportunities as indicated by a rise in their share of employment, but that this effect is dampened by patriarchal cultural norms whose strength is measured by the proportion of the population tracing its ancestry to ethnic groups who adopted the plough as an agricultural implement. That aggregate technical efficiency rises in women's share of employment is consistent with improvement in the average quality of the workforce when talented women's entry to it is eased. That this effect is dampened by patriarchal cultural norms is consistent with their promoting a misallocation of employed women. Additionally, aggregate technical efficiency appears improved by democracy, the control of corruption, and trade-openness.
Keywords: J16; 330; gender equity; patriarchy; aggregate productivity; stochastic frontier model; technical efficiency